CULTUROLOGICAL ASPECT OF MARITIME SPECIALIST OCCUPATIONAL TRAINING - Vera Tenishcheva; Yuliya Kuznetsova; Larisa Fishkova; Elena Tsyganko (Вестник Северо-Кавказского федерального университета, 2022)
Maritime specialist training involving cultural aspects of his work has been analyzed in the article. The classification of typical tasks of his work in terms of intercultural communication in a foreign language environment associated with the contact, distant and mediated communication is enclosed. The aims of special course «Psychological basis of crew management» designed at the Department of Foreign Languages of the SMU named after Admiral F. F. Ushakov for the mariners were listed. It is shown that the use of the case study method during the development of the professional standard tasks in a multicultural environment develops student's orientation in the socio-cultural and ethno-cultural peculiarities of specialists of other nationalities.